La prensa del “Proceso”. El diario Convicción durante la dictadura militar argentina (1976-1983) - Saborido, Jorge; Borrelli, Marcelo (Estudios sobre el Mensaje Periodístico, 2008)
The newspaper Convicción was born in 1978 as way of press linked to two political fundamental actors of the argentinian dictatorial period: admiral Emilio Massera and the Argentine navy. His appearance was thought-out as a platform for the political throwing of admiral Massera and in turn a space of propping-up for the interests of the navy inside the internal military one. In this work we propose to revise the conditions of emergence and development of the newspaper as well as his principal publishing positions during particularly excellent different historical moments of the military Argentine dictatorship (1976-1983).
Keywords: The military Argentine dictatorship; Argentine press; Newspaper Conviccion; Massera